2019
DOI: 10.1177/2050313x19850353
|View full text |Cite
|
Sign up to set email alerts
|

Koebner phenomenon in leukocytoclastic vasculitis: A case report and an updated review of the literature

Abstract: Leukocytoclastic vasculitis is the most common form of cutaneous vasculitis. It is a neutrophilic small vessel vasculitis resulting from the deposition of circulating immune complexes. Henoch-Schonlein purpura is a systemic type of leukocytoclastic vasculitis, characterized by immunoglobulin A-mediated blood vessel injury. We present a case of Henoch-Schonlein purpura in an adult female manifesting with a vasculitic rash with Koebner phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Further research is warranted to establish the role of COVID-19 behind the causation (if any). 6,7,8,9 Our case of post-Covid cutaneous small-vessel vasculitis with features of Koebnerization highlights the fact that COVID-19 may be associated with cutaneous manifestations even after recovery.…”
Section: I Scl a I M Ermentioning
confidence: 71%
“…Further research is warranted to establish the role of COVID-19 behind the causation (if any). 6,7,8,9 Our case of post-Covid cutaneous small-vessel vasculitis with features of Koebnerization highlights the fact that COVID-19 may be associated with cutaneous manifestations even after recovery.…”
Section: I Scl a I M Ermentioning
confidence: 71%
“… 7 Unlike our case, most reported cases of Koebner phenomenon in LCV were secondary to Henoch-Schonlein purpura or medications. 8 One of the proposed mechanisms of koebnerization is immunoglobulin aggregation at sites of inflammation. 7 Thus, it is often associated with pruritic conditions where scratching stimulates local inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory dermatosis [154] Coffin-Siris syndrome [155] Churg-Strauss syndrome [156] Cryoglobulinemia [157] Leukocytoclastic vasculitis [158] Drug reaction (Labetalol, Clindamycin, Sorafenib) [159][160][161][162] Virus infection (Hand-foot-andmouth disease, Virus varicella zoster) [163,164] one case study reported that a patient with psoriasis vulgaris developed a new psoriatic lesion following tissue dilator insertion after total mastectomy for right breast cancer. These findings indicate that mechanical stretch-induced lesions as a consequence of KP.…”
Section: Vaccination [129]mentioning
confidence: 99%